Superluminescent laser-integrated nanocarbonized matrix pumping the neodymium lasers YAG:Nd - Onachenko, M.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Forming of surface nanocarbonized structures on substrate, it is possible to reduce the series resistance of nanoregions contacts in heterostructures. It was achieved by increasing the efficiency and output power in nanocarbonized structures by 2 times with decreasing the heat release on successive contact resistance. We obtained improved parameters of nanocarbonized matrices for pumping after finding the possibility to create a new generation of neodymium lasers with semiconductor pumping without forced cooling. The obtained III-nitride AlGaInN/Si heterostructures instead of the AlGaAs/GaAs ones allow to more accurately select and grow the better chemical composition for the emitting region, the emission spectrum of which is closer to the radiation of a neodymium laser.